Cancer and mortality in coal mine workers: a systematic review and meta-analysis. Issue 5 (15th November 2021) - Alif, Sheikh M; Sim, Malcolm R; Ho, Clarence; Glass, Deborah C
Abstract : Coal mine workers are exposed to a number of workplace hazards which may increase the risk of cancer and mortality. We conducted a systematic review and meta-analysis to investigate cancer and mortality in coal mine workers We searched in Ovid Medline, PubMed, Embase and Web of Science databases using keywords and text words related to coal mines, cancer and mortality and identified 36 full-text articles using predefined inclusion criteria. Each study's quality was assessed using the Newcastle-Ottawa Scale. We performed random-effect meta-analyses including 21 of the identified articles evaluating cancer and/or mortality of coal mine workers. The meta-analysis showed an increased risk of all-cause mortality (SMR 1.14, 95% CI 1.00 to 1.30) and mortality from non-malignant respiratory disease (NMRD) (3.59, 95% CI 3.00 to 4.30) in cohorts with coal workers' pneumoconiosis (CWP). We found a somewhat increased risk of stomach cancer (1.11, 95% CI 0.97 to 1.35) and of mortality from NMRD (1.26, 95% CI 0.99 to 1.61) in the cohorts of coal miners with unknown CWP status. The meta-analysis also showed a decreased risk of prostate cancer and cardiovascular and cerebrovascular mortality among coal miners. This may be a result of the healthy worker effect and possible lower smoking rates, and perhaps also reflect the physically active nature of many jobs in coal mines. The meta-analysis for lung cancer did not show increased risk in coal miners with CWP (1.49, 95% CI 0.70 to 3.18) or for coal miners of unknown CWP status (1.03, 95% CI 0.91 to 1.18). Lower smoking rates in coal mine workers could explain why case–control studies where smoking was controlled for showed higher risks for lung cancer than were seen in cohort studies. Coal mine workers are at increased risk of mortality from NMRD but decreased risk of prostate cancer and cardiovascular and cerebrovascular mortality. Studies of coal mine workers need long-term follow-up to identify increased mortality and cancer incidence.